Utilization of Nipa Leaves Meal (Nypa fruticans Wurmb) as a Substitute for Rice Bran of Striped Catfish Feed (Pangasius hypophthalmus) - Mukti, Retno Cahya; Amin, Mohamad; Yulisman, Yulisman; Tanbiyaskur, Tanbiyaskur; Sari, Melia Intan; Suriyanti, Su Nyun Pau (Journal of Aquaculture and Fish Health, 2024)
Feed is one of the important components of aquaculture. The higher the feed price, it is necessary to look for alternative materials for feed ingredients. One of the alternative feed ingredients that can be used is rice bran. In certain seasons, rice bran production decreases. One of the ingredients that can be used as a substitute for rice bran is nipa leaves. This study aims to determine the effect of using nipa leaves meal to replace rice bran in feed formulations and to examine the best percentage of nipa leaves meal on the growth and survival of striped catfish. This study used a completely randomized design (CRD) which consisted of 5 treatments (P) with three replications, namely P0 (0% nipa leaves meal: 20% rice bran), P1 (5% nipa leaves meal: 15% rice bran), P2 (10% nipa leaves meal: 10% rice bran), P3 (15% nipa leaves meal: 5% rice bran), and P4 (20% nipa leaves meal: 0% rice bran). The size of fish used in this study was 4±0.5 cm with a sticking density of 1 fish/L. The rearing of the study was 42 days. Research results show that using nipa leaves meal as a substitute for rice bran with different significantly affects the growth of absolute weight, absolute length, feed efficiency, and protein efficiency ratio. Research results show that the P4 treatment with a percentage of 20% nipa leaves meal: 0% rice bran is the best result with absolute weight growth (2.70 g), absolute length growth (3.35 cm), feed efficiency (85.88%), the protein efficiency ratio (2.66%), and survival (100%). Water quality obtained during rearing is temperature 25.2–31.2oC, pH 6.9–8.7, and dissolved oxygen (DO) 5–6.1 mg/L.